2022
DOI: 10.1038/s41413-022-00206-z
|View full text |Cite
|
Sign up to set email alerts
|

Specific inflammatory osteoclast precursors induced during chronic inflammation give rise to highly active osteoclasts associated with inflammatory bone loss

Abstract: Elevated osteoclast (OC) activity is a major contributor to inflammatory bone loss (IBL) during chronic inflammatory diseases. However, the specific OC precursors (OCPs) responding to inflammatory cues and the underlying mechanisms leading to IBL are poorly understood. We identified two distinct OCP subsets: Ly6ChiCD11bhi inflammatory OCPs (iOCPs) induced during chronic inflammation, and homeostatic Ly6ChiCD11blo OCPs (hOCPs) which remained unchanged. Functional and proteomic characterization revealed that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“… 57 Also, our TRAP staining verified that overactivated osteoclasts were blamed for inflammatory bone loss. 58 , 59 For treatment, intervening in the primary diseases and inhibiting inflammation are given priority. Thus, inhibiting immune cells, cytokine, osteoclastogenesis, and osteoclast activity is applicable.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Also, our TRAP staining verified that overactivated osteoclasts were blamed for inflammatory bone loss. 58 , 59 For treatment, intervening in the primary diseases and inhibiting inflammation are given priority. Thus, inhibiting immune cells, cytokine, osteoclastogenesis, and osteoclast activity is applicable.…”
Section: Discussionmentioning
confidence: 99%
“…As a causative substance of Staphylococcus aureus , the most common pathogenic bacteria in clinical practice, HKSA is often used as an inflammatory inducer [ 16 , 17 , 18 , 19 ]. There is considerable evidence to show that chronic inflammation can lead to osteoporosis by inhibiting the osteogenic activity of osteogenic cells [ 22 , 23 , 24 ] or by promoting the bone resorptive activity of osteoclasts [ 23 , 24 , 25 ]. This study found that HKSA caused an increase in the number of OCN + cells, suggesting that HKSA may mainly lead to bone loss by inhibiting the osteogenic activity of osteogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 These proinflammatory factors have also been shown to expand a highly active osteoclast population derived from the Ly6C high /CD11b high cells. 138 Among these proinflammatory factors, IL-1 has been suggested to play a significant role in hematopoietic aging and myeloid malignancies.…”
Section: Skeletal Aging and The Bone Marrow Microenvironmentmentioning
confidence: 99%